Preclinical evidence of a direct pro-survival role of arginine deprivation in multiple myeloma - Trudu, Matteo; Oliva, Laura; Orfanelli, Ugo; Romano, Alessandra; Di Raimondo, Francesco; Sanvito, Francesca; Ponzoni, Maurilio; Cenci, Simone (Frontiers in Oncology, 2022)
Multiple myeloma grows by establishing multiple interactions with bone marrow cells. These include expansion of myeloid-derived suppressor cells, which drive immunoevasion via mechanisms that include arginase-1-driven depletion of L-arginine, thus indirectly promoting myeloma cell survival and tumor progression. The peculiar biology of malignant plasma cells postulates that arginine depletion may benefit their fitness also directly, e.g., by engaging the integrated stress response, or by stimulating autophagy through mTORC1 inhibition. We thus investigated the direct impact of arginine deprivation on myeloma cells and challenged its pathophysiological relevance in vitro and in vivo. First, we found that partial arginine depletion spared proliferation of human multiple myeloma cells at concentrations that arrest human T cells. Next, we asked if arginine shortage activates putative adaptive pathways in myeloma cells. Low arginine failed to activate the integrated stress response, as indicated by unmodified phosphorylation of the eukaryotic initiation factor 2 alpha, but sizably inhibited mTORC1, as revealed by reduced phosphorylation of ribosomal protein S6. Notably, depressed mTORC1 activity was not sufficient to increase autophagy, as assessed by the lysosomal digestion rate of the autophagosome-associated protein, LC3-II. Rather, it stimulated mTORC2, resulting in increased phosphatidylinositol-3 kinase-dependent AKT phosphorylation and activity, leading to heightened inhibitory phosphorylation of the pro-apoptotic BAD protein. We then tested whether arginine depletion-activated AKT may protect malignant plasma cells from cell death. Indeed, culturing myeloma cells in low arginine medium significantly reduced the apoptotic effect of the first-in-class proteasome inhibitor, bortezomib, an outcome prevented by pharmacological inhibition of AKT phosphorylation. Finally, we challenged the relevance of the identified circuit in vivo. To gauge the pathophysiologic relevance of low arginine to myeloma growth independently of immunoevasion, we xenotransplanted human myeloma cells subcutaneously into T cell-deficient Rag2–/– gamma chain–/– recipient mice and treated palpable tumor-bearing mice with the clinical-grade arginase inhibitor CB1158. Arginase inhibition significantly raised serum arginine concentration, reduced tumor growth by caliper assessment, and decreased intra-tumor AKT phosphorylation in vivo. Altogether, our results reveal a novel direct pro-survival effect of arginine deprivation on myeloma cells, with potential therapeutic implications.